Rhamnogalacturonan II: Chemical Synthesis of a Substructure Including α‐2, 3‐Linked Kdo. Issue 24 (9th April 2021) - Mancuso, Enzo; Romanò, Cecilia; Trattnig, Nino; Gritsch, Philipp; Kosma, Paul; Clausen, Mads H.
Abstract: The synthesis of a fully deprotected Kdo‐containing rhamnogalacturonan II pentasaccharide is described. The strategy relies on the preparation of a suitably protected homogalacturonan tetrasaccharide backbone, through a post‐glycosylation oxidation approach, and its stereoselective glycosylation with a Kdo fluoride donor. Abstract : Chemical synthesis of a Kdo‐containing rhamnogalacturonan II pentasaccharide was achieved by a [4+1] post‐glycosylation oxidation approach.